When to start a new firm? Modelling the timing of novice and serial entrepreneurs - Thomas Gries; Wim Naudé (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
The success of new start-up firms often depends on timing. It is valuable for the potential entrepreneur to wait for the right moment before starting a new firm. In this paper we provide a theoretical model to determine the optimal time for starting a new firm. We integrate insights from the real option theory with the theory on entrepreneurial market entry. An important and novel feature of our model is that it allows the start-up timing decisions of novice and serial entrepreneurs to be distinguished.
Keywords: D92; D81; L26; M3; 330; entrepreneurship; serial entrepreneurship; start-ups; real options; stochastic optimal control; Unternehmensgründung; Zeit; Theorie